Morphological and Histological Structure of the Liver in Budgerigar (Melopsittacus undulatus ) - R. Mohsin, Aveen; H. Hameed, Zahraa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Morphological description and histological structure of the liver have been studied in Durra bird Melopsittacus undulatus. The liver is a bilobed organ , the left lobe with three secondary lobes and slightly larger than the right lobe which is elliptical in shape. Liver is surrounded by a capsule that consists of thin layer of connective tissue with no distinction between interlobular septa . The parenchyma tissue consists of hepatic cells arranged with thickness 2_1 cell. Portal area appears within the liver parenchyma tissue composed of hepatic artery, portal vein and bile duct and supported by connective tissue. A gallbladder was not noticed in this species.